The Role of the Organizational Effectiveness of Human Resources in Developing of the Company: an Analytical Study for a Sample of Iraqi Industrial Companies Listed on the Iraq Stock Exchange Administrative Structure - Nazim Matrud, Sabih; Manea Lafta, Alaa (International Journal of Psychosocial Rehabilitation, 2020)
The research aims to know the role exercised by the organizational effectiveness of human resources in developing the administrative structure of industrial companies through attracting human experiences that reflect on increasing and rationalizing their horizons on modern strategic systems in a way that develops their administrative reality. The research has been applied to a sample of Iraqi industrial companies listed on the Iraq Stock Exchange for the financial period from (2013-2018).Through the analysis of their data, the research objectives have been reached and hypothesis tested.The most important findings of the research is that human resources are of the most important knowledge resources owned by companies and which must be given great importance due to its impact, as a topic, on the various activities in the company as well as the impact on rational spending operations on rewards and training courses for the human cadre in companies as regards developing their organizational activities. The most important thing recommended by the research is the necessity of starting to understand the philosophy of human knowledge management in industrial companies Hough the importance and connections with other variables as well as interest in human resources and their components which represent the intellectual resources that affect the various areas of the company's work.